A comparative study of pre-service teachers’ knowledge and perceptions of, and attitudes toward, inclusive education - Jacob, Udeme Samuel; Pillay, Jace (Frontiers in Education, 2022)
This study examined pre-service teachers' knowledge and perceptions of, and attitudes towards, inclusive education. A total of 131 pre-service teachers from two programmes – one at a College of Education and a university programme through the Faculty of Education – were surveyed using a cross-sectional survey research design. Data were collected using a self-developed questionnaire. The questionnaire was pilot tested among pre-service teachers from the Faculty of Education at a university which did not participate in the study. We used a 3 × 2 factorial multivariate analysis of variance (MANOVA) to analyse the descriptive and inferential data (means, standard deviations). The study revealed a statistically significant difference between pre-service teachers’ gender (male and female) and programmes (university and college of education) regarding their knowledge and perceptions of, and attitudes towards, inclusive education. The results indicated a significant MANOVA. In the follow-up analysis of the variance test, pre-service teachers’ perceptions and attitudes differed between genders and programmes. In addition, the study found a significant difference between pre-service teachers’ perceptions and attitudes toward inclusive education based on their educational programmes. Pre-service teachers from the College of Education scored higher than those from the Faculty of Education at a university. We discuss the implications of an egalitarian learning environment.